Turkey's military operations in Syria and Iraq - Salim Çevik (Stiftung Wissenschaft und Politik (SWP), 2022)
In the early hours of 18 April, Turkish Armed Forces (TAF) launched a military operation inside Northern Iraq dubbed Claw-Lock. Simultaneously, Turkey intensified its military activities in Syria. Furthermore, on 23 May, President Tayyip Erdoægan announced that Turkey will soon start a new military operation in Syria. These moves reflect Turkey's new military strategy, based on area control, against the Kurdistan Workers' Party (PKK). So far, this new approach has yielded military success. However, it is precisely military success that is reinforcing the tendency to deal with the Kurdish problem only in terms of security and military solutions and to rule out any long-term political solution to the problem. Europe should continue to support efforts towards seeking a solution that also addresses the political dimensions of the problem.
Keywords: 320